An intriguing morphological variability of Platanthera s.l. - Petr G. Efimov (European Journal of Environmental Sciences, 2012)
The morphology of 38 species of the genus Platanthera s.l. was investigated by means of light and electron microscopy. Particular attention was paid to the structure of gynostemium and pollinaria. The species investigated represent 10 major lineages of the genus, all being recognized as sections or segregate genera in various taxonomical treatments. Considerable morphological variability was confirmed for Platanthera s.l. The most notably variable structures are tuberoids (root-like, stoloniferous, spherical, etc.), lip (entire, lobed, fimbriate etc.), rostellar lateral lobes (flat, concave, bursicle-like), lateral stigma lobes (flat, protruding, etc.) and viscidia (orbicular, lanceolate, sub-linear, deeply concave, reduced). The morphology of several taxa confirms that they do not belong to Platanthera s.l., of them Platanthera camtschatica displays relation to Galearis s.l. and P. latilabris, P. clavigera and P. biermanniana – to subtribe Habenariinae. In many cases the morphology confirms the monophyly of the lineages within Platanthera s.l., as Tulotis, Limnorchis etc., although more thorough sampling is needed. Some of those groups correspond to the clades as defined by previously published molecular phylogenies (Hapeman and Inoue 1997, Bateman et al. 2009). The morphological polymorphism in Platanthera s.l. (especially gynostemium structure) seems to be higher than in many other large genera of the subtribe Orchidinae, as Dactylorhiza, Ophrys or Orchis, and led to recognition of several segregate genera within Platanthera s.l. However, lesser genetic polymorphism revealed by molecular markers gives evidence for morphological plasticity (in particular, in gynostemium structure) and rapid morphological evolution of this group.